Kepemimpinan Kepala Desa Dalam Mewujudkan Desa Berkembang Di Desa Balayo Kecamatan Patilanggio Kabupaten Pohuwato - Umar Sune; Rusni Djafar; Rosna Sakula (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
This research aims to examine the role of village leadership in realizing a developed village in Balayo Village, Patilanggio District, Pohuwato Regency. The study focuses on the leadership style of the village head and its impact on the development efforts within the community. By utilizing a qualitative approach, this research involves in-depth interviews with village leaders, community members, and local stakeholders, along with field observations. The findings reveal that effective leadership is crucial in fostering community participation, facilitating infrastructure development, and improving social welfare. The village head's vision, communication skills, and decision-making processes were identified as key factors in achieving village development goals. This study contributes to the understanding of local governance and offers insights into how leadership can drive rural development in Indonesia.